INSTITUTIONAL FACTORS AS CONDITIONS FOR CREATING VALUE FOR STRATEGIC NETWORK STAKEHOLDERS - Plakhin , Andrey; Ogorodnikova, Ekaterina; Khokholush , Maria; Guseva, Tatiana; Selezneva, Maria (Revista Inclusiones, 2020)
The relevance of the study is due to the need to determine the factors of the stakeholder and institutional environment that stimulate the development of industrial production. The study is based on materials from state authorities on the situation and the development of institutional conditions for doing business, as well as materials from companies collected in the SPARK-interfax information and analytical database. A multiple regression model is used as a method for determining the dependence of the formation of stakeholder value due to the factors of the institutional environment. In this model, the performance indicators of network stakeholders are used as the resulting indicator, and the characteristics of the institutional environment are recognized as factor indicators. The results allow us to identify several factors of the institutional environment that affect the stakeholders of the strategic network of the Titanium cluster, such factors include the availability of funding and simplification of administrative procedures.